ANALISIS PROGRAM PENDIDIKAN VOKASI DALAM MENGHADAPI TANTANGAN INDUSTRI - Riska Angriani; Irjus Indrawan; Alridho Fransiska; Siti Naimah (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to analyze the relevance of vocational education programs in Indonesia to the challenges facing industry today. This research uses a descriptive qualitative research type by descriptively explaining qualitative data taken from various articles. The method used is systematic literature review (SLR). The research results show that there is a gap between the skills provided by vocational education institutions and actual needs in the field. For this reason, regular curriculum updates are needed, improving the quality of technology-based teaching, as well as strengthening cooperation between vocational education institutions and industry to create more effective synergies.